2017
DOI: 10.18203/2320-1770.ijrcog20171442
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analytical study of total abdominal hyeterectomy for benign gynaecological conditions

Abstract: Background: Hysterectomy, which is one of the most common surgeries performed on women, dates back to ancient time. This retrospective study was done to determine a baseline data on various indications for total abdominal hysterectomy for benign gynaecological conditions, most common presenting symptoms, and socio-economic status and their histopathology correlation.Methods: This retrospective study was performed in the department of Obstetrics and gynaecology, in collaboration with Department of Pathology, Ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…This relatively high frequency of leiomyomas in our study is consistent with studies conducted by Pathak V et al 14 and Baral R et al, 3 both of whom found 49.78% and 48.6% frequency of leiomyoma respectively. In contrast lower values were observed in other studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This relatively high frequency of leiomyomas in our study is consistent with studies conducted by Pathak V et al 14 and Baral R et al, 3 both of whom found 49.78% and 48.6% frequency of leiomyoma respectively. In contrast lower values were observed in other studies.…”
Section: Discussionsupporting
confidence: 93%
“…12 Minimally invasive procedures are now available as alternate option of hystrectomy but not widely used due to untrained staff, expenses and non availability in many health centers. 13,14 Histopathological analysis of the hysterectomy specimens should be undertaken for justification of procedure and diagnostic purposes. 15 This research was aimed to ascertain frequency and morphology of different benign histopathological lesions in TAH specimens.…”
Section: Introductionmentioning
confidence: 99%
“…8 Authors found were similar with study by Pathak et al, who found that most common indication for TAH for benign gynaecological condition was fibroid uterus in 49.78%, abnormal uterine bleeding in 11.01%, adenomyosis in 9.25%, Ovarian mass in 8.81%, chronic cervicitis in 8.37% and AUB in 6.60%. 12 In present study, histo-pathological diagnosis was leiomyoma in 55 (55%), adenomyosis in 30 (30%), endometrial polyp in 5 (5%), endometrial hyperplasia in 5 (5%) and serous cystadenoma of ovary in 5 (5%).…”
Section: Discussionmentioning
confidence: 44%
“…12 In present study, abdominal hysterectomy was performed in 46 (46%) patients, vaginal hysterectomy in 44 (44.33%) patients while laparoscopic hysterectomy was performed in 5 (6.66%) patients. Contrast to our study, Tan et al found that TAH was done in 78.4%, LAVH in 13.0% and vaginal hysterectomy in 8.6%.…”
Section: Discussionmentioning
confidence: 66%
“…8 Authors found similar results with study by Pathak et al, who found that most common indication for TAH for benign gynaecological condition was fibroid uterus in 49.78%, abnormal uterine bleeding in 11.01%, adenomyosis in 9.25%, Ovarian mass in 8.81%, chronic cervicitis in 8.37% and AUB in 6.60%. 9 In present study, abdominal hysterectomy was performed in 46 (46%) patients, vaginal hysterectomy in 44 (44.33%) patients while laparoscopic hysterectomy was performed in 5 (6.66%) patients (Table 4). …”
Section: Discussionmentioning
confidence: 63%